Effectiveness of Problem Solving Learning Model towards Student Learning Outcomes on Acid-Base Solution in SMA Negeri 1 Buko on Academic Year 2018-2019 - Yulianti Siako; Kasmudin Mustapa (Universitas Tadulako, 2020)
This study aimed to determine the effectiveness of problem-solving learning models on students’ learning outcomes in the acid-base solutions topic in SMA Negeri 1 Buko on Academic Year 2018-2019. This type of research was a true experiment with a non-randomized posttest two group design. The population of this research was all students of class XI MIA, the sampling techniques was saturated sampling methods. The sample used was students of class XI MIA 1 and XI MIA 2 as experimental class 1 and experimental class 2. The testing of students’ learning outcomes data was using one-party statistical analysis t-test to test the completeness of individual learning outcomes and classical completeness test to test the overall percentage of mastery learning. The results of data analysis obtained, the mean experimental class 1 (X1) was 75.5 with a standard deviation of 10.71 and the average experimental class 2 (X2) was 76.43 with a standard deviation of 12.77. The results of hypothesis testing with one-party t-test statistics in the experimental class 1 and 2 was obtained tcount > ttable (2.321 > 1.740; 2.306 > 2.101) with a significance level of α = 0.05 and degrees of freedom 18 and 19, then H0 was rejected and Ha was accepted. Then, the result of the classical completeness test obtained in the experimental class 1 were 80% and experimental class 2 were 80.95%. Based on the results of data analysis it can be concluded that the problem-solving learning model is effective against students’ learning outcomes in the acid-base solutions topic in SMA Negeri 1 Buko on Academic Year 2018-2019.